Fluorescence Imaging Using Methylene Blue Sentinel Lymph Node Biopsy in Melanoma. (August 2022) - Cwalinski, Tomasz; Skokowski, Jarosław; Polom, Wojciech; Marano, Luigi; Swierblewski, Maciej; Drucis, Kamil; Roviello, Giandomenico; Cwalina, Natalia; Kalinowski, Leszek; Roviello, Franco; Polom, Karol
Introduction: Fluorescence imaging of sentinel node biopsy in melanoma is a novel method. Both indocyanine green (ICG) and methylene blue (MB) have fluorescent properties. The aim of this study was to present, for the first time in a clinical series of patients, the possible usage of MB as a fluorescent dye for sentinel node biopsy during surgery for melanoma. Material and methods: Twenty patients with skin melanoma, who were candidates for sentinel node biopsy were enrolled in our study. All patients underwent simultaneous use of standard nanocolloid and blue dye. Transcutaneous visualization of the sentinel node, visualization of lymphatic channels as well as sentinel node fluorescent visualization were all measured. We also performed calculations of Signal to Background ratios (SBR). Results: In 15% (3/20) of patients, the fluorescent sentinel node was visible through the skin. The median SBR for the sentinel node visualization by fluorescence was 3.15 (range, 2.7–3.5). Lymphatic channels were visible in lymphatic tissue via fluorescence before visualization by the naked eye in 4 patients (20%). The median SBR ratio was 3.69 (range, 2.7–4.2). Sentinel nodes were visible by fluorescence in 13 cases (65%). The median SBR ratio was 2.49 (range, 1.5–5.7). No factors were found to be associated with fluorescent MB visualization of a sentinel node during biopsy. Conclusion: This is the first clinical study presenting the usefulness of fluorescent sentinel node biopsy in melanoma patients using MB as a fluorophore. Further studies are necessary to provide methods for its' clinical implementation.